Development of Industrial Tribology in China - Qunji Xue (Japanese Society of Tribologists, 2007)
The Chinese industries are facing tough international competition, huge environmental pressure, government requirement for improved efficiency and lower emissions from the tribological and lubricating systems and rapid technological developments. A brief review on industrial tribology progress in China was outlined in this paper. The special characteristics of industrial tribology, the problem and the challenges in Chinese industrial tribology were discussed. At last, our insights and perspectives on future trends in industrial tribology in China will also be reviewed.